In situ-generated Co@nitrogen-doped carbon nanotubes derived from MOFs for efficient hydrogen evolution under both alkaline and acidic conditions. (4th September 2017) - Li, Ji-Sen; Du, Bing; Lu, Zhi-Hua; Meng, Qing-Ting; Sha, Jing-Quan
Abstract : In situ -generated Co@nitrogen-doped carbon nanotubes derived from metal–organic frameworks were fabricated by a facile method and corresponding HER performances were investigated in detail. Abstract : Electrocatalytic water splitting producing hydrogen is of great importance for renewable energy storage and conversion technologies. In recent years, low-cost and high-efficiency electrocatalysts for the hydrogen evolution reaction (HER) have attracted a lot of attention. Herein, we report that in situ -generated Co@nitrogen-doped carbon nanotubes (Co@NCNTs) derived from metal–organic frameworks (MOFs) were fabricated by a facile method and corresponding HER activities were investigated in detail. Among these hybrids, the Co@NCNTs-800 hybrid shows outstanding electrocatalytic activity and stability, which is one of the best Co-based electrocatalysts for the HER under both alkaline and acidic conditions reported to date, benefiting from the synergistic effect from Co nanoparticles, N dopants, and CNTs. Most importantly, this work paves a new way for designing novel, efficient, and inexpensive HER electrocatalysts derived from MOFs as promising alternatives to Pt or Pt-based materials.